Pembuatan Barcode Produk Industri Meubel dan Furniture untuk Mendukung Ekspor Produk Ber-Sertifikat Legalitas Kayu - Rahmanta Setiahadi; Denies Priantinah S; Djoko Setyo Martono (Universitas Merdeka Madiun, 2021)
Timber Legality Certificate is to meet the requirements of the legality of timber for the forest industry. Application of timber legality verification system allows Indonesia opened wider timber market, especially European market, through the signing of the Voluntary Partnership Agreement (VPA) in September 2013. The forestry industry, timber legality certificate must fulfill in order to be able to do eskport product. Must to get the V-legal documents in any export activity forestry product timber legality certified consequences must be applied to production management system and marketing system. The research objective is to create a system of production information via barcode for small industries that already have a certificate of Timber Legality. The results showed that the ability to prepare the production and marketing of information systems to support the administration of V-legal documents in the export activities for small industries, a serious problem in meeting the document export goods. Therefore, barcode software development program to help solving the problems facing SMEs in the furniture industry and furniture administrating V-legal documents.